"At Such a Good School, Everybody Needs It": Contested Meanings of Prescription Stimulant Use in College Academics. (September 2017) - Cooper, Amy; McGee, Lisa
Abstract: Approximately 15% of US college students have used Adderall or other stimulant medications without a prescription or not as prescribed. The development of college academics into a field of practice amenable to unauthorized pharmaceutical intervention suggests a growing acceptance of pharmaceutical self‐fashioning among young people in the United States. However, analyzing illicit stimulant use from college students' perspectives, we documented significant contestation over the practice's acceptability. For some, unauthorized stimulant use violated the rules of fair play, but for others it was an understandable strategy to gain an edge and maximize one's "return on investment." Viewing college academics in market‐oriented terms encouraged students to understand illicit stimulant use as an expectable (if not always morally acceptable) strategy for managing the competition of college life and a postrecession job market. This analysis shows how the moral valence of unauthorized stimulant use is strongly shaped by the sociocultural context that shapes people's realities.